User-Centered Computer Aided Language Learning - Zaphiris, Panayiotis (Information Science Pub., 2006)
"This book discusses the basis of a broad framework for the development and management of Computer Aided Language Learning (CALL) environments, covering domains as diverse as education, information systems, psychology, sociology, linguistics, artificial intelligence and e-learning"--Provided by publisher.